2020
DOI: 10.1088/1361-6463/ab713a
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of trap and recovery characteristics based on low-frequency noise for E-mode GaN HEMTs with p-GaN gate under repetitive short-circuit stress

Abstract: In this letter, the degradation and recovery characteristics of E-mode AlGaN/GaN high-electron mobility transistors (HEMTs) were investigated under repetitive short-circuit (SC) stress. Output, transfer, transconductance and gate-leakage characteristics were analyzed in detail before and after repetitive SC stress. After stress, the electrical characteristics of the devices gradually degraded as the SC pules increased. Low-frequency noise measurements are performed over the frequency range of 1 Hz–10 KHz by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Based on literature, three mechanisms apply during stress but not to the same extent. First charge trapping under gate electrode is responsible for threshold voltage shift [6].…”
Section: Resultsmentioning
confidence: 99%
“…Based on literature, three mechanisms apply during stress but not to the same extent. First charge trapping under gate electrode is responsible for threshold voltage shift [6].…”
Section: Resultsmentioning
confidence: 99%
“…Based on literature, three mechanisms apply during stress but not to the same extent. First charge trapping under gate electrode is responsible for threshold voltage shift [6]. Trapping in drain access region causes decrease of free charge in the 2DEG [7] and both trapping effects are decreasing mobility of carriers in the 2DEG [8] affecting on-resistance and saturation current.…”
Section: Resultsmentioning
confidence: 99%
“…This pulsed negative V GS bias stress modulates the negatively charged trap density with an increase in V GS bias stress and increase in stress pulse (t stress ). However, the p-GaN gate HEMT device structure has no oxide layer compared with the MIS-HEMT device, which tells us that the reported surface state trapping mechanisms with oxide layer are not applicable here, although some research on the reliability of commercialized E-mode GaN HEMT with p-GaN gate under reverse electrostatic discharge stress and repetitive short circuit stress has reported that the degradation mechanism could be addressed by the formation of traps at the barrier layer, p-GaN/AlGaN hetero-interface, and AlGaN/GaN interface [26,27]. At the present work, we studied the degradation behavior and mechanism for the impact of various negative gate stress voltage pulses without drain stress bias at room temperature.…”
Section: Gate-lag Effectmentioning
confidence: 91%